THE PROBLEMS OF PROVIDING AGRICULTURE OF THE RA WITH THE STAFF OF AGRICULTURAL SPECIALTIES AND THE WAYS OF THEIR SOLUTION - Акопян, Л. Л. (Scientific Progress & Innovations, 2013)
Due to the lack of specialists directly in the field, the agriculture of Armenia losses one third of gross production. The article substantiates the necessity of such personnel and gives the basic ways of their content, sources of funding salaries, the basic principles for a share of each source and the particular dimensions of the share of the conditions of production, location, etc. The main sources of funding for the salary are the state and a private sector of farming, to which agricultural specialists will provide services.